Правова природа одноразової грошової допомоги у разі смерті військовослужбовця - Кухарєв, О. Є.; Kukhariev, O. Ye.; Олександр Кухарєв (Правова держава. – 2024. – Вип. 55. – С. 104–122, 2024)
The article is devoted to the clarification of the legal nature of one-time monetary assistance in the event of the death of a serviceman, as well as the corresponding personal order regarding this assistance in the event of his death. It is a well-founded position that such assistance is not an element of the composition of the inheritance, taking into account its specific features. Thus, unlike the heirs, recipients of the aid under investigation do not acquire the duties of a deceased serviceman and are not required to notify creditors of the latter’s death. In addition, the right to receive a one-time cash benefit in the event of the death of a serviceman is exercised within three years from the date of the emergence of such a right, which is related to the date specified in the person’s death certificate. Recipients of one-time cash assistance do not coincide with the circle of heirs according to the law of the first order. It is emphasized that the terminology of inheritance law does not apply to such assistance. In particular, persons who are entitled to receive a one-time cash benefit are not named as heirs, the time of the death or death of a serviceman is not indicated as the time of the opening of the inheritance, etc. The right to receive the researched assistance arises as a result of the person’s death, which makes inheritance impossible in this case. The essence of universal legal succession is the transfer of rights and obligations from the testator to his heirs. It is emphasized that the one-time monetary assistance in the event of the death of a serviceman has a compensatory nature, which is aimed at materially supporting family members (parents, children, spouse) and dependents of a deceased serviceman after the loss of a loved one. A military serviceman’s personal order to pay a one-time cash benefit to a certain person in the event of his death (death) is not a type of will. In its essence, this personal order is close to the order of a depositor of a bank (financial institution) in the event of his death, which is defined in Part 1 of Art. 1228 of the Civil Code of Ukraine.

Стаття присвячена з’ясуванню правової природи одноразової грошової допомоги у разі загибелі військовослужбовця, а також відповідного особистого розпорядження стосовно цієї допомоги на випадок своєї смерті. Обґрунтована позиція, що така допомога не є елементом складу спадщини, зважаючи на притаманні їй особливості. Так, отримувачі досліджуваної допомоги, на відміну від спадкоємців, не набувають обов’язків померлого військовослужбовця та не зобов’язані повідомляти кредиторів про смерть останнього. Крім того, право на отримання одноразової грошової допомоги у разі загибелі військовослужбовця здійснюється протягом трьох років з дня виникнення такого права, що пов’язане з датою, зазначеною у свідоцтві про смерть особи. Отримувачі одноразової грошової допомоги не збігаються з колом спадкоємців за законом першої черги. Підкреслено, що стосовно такої допомоги не застосовується термінологія спадкового права. Зокрема, особи, які наділені правом на отримання одноразової грошової допомоги, не пойменовані як спадкоємці, час смерті чи загибелі військовослужбовця не позначається як час відкриття спадщини тощо. Право на отримання досліджуваної допомоги виникає внаслідок смерті особи, що унеможливлює спадкове правонаступництво у цьому разі. Сутність універсального спадкового правонаступництва становить перехід прав та обов’язків від спадкодавця до його спадкоємців. Наголошено, що одноразова грошова допомога в разі загибелі військовослужбовця має компенсаторний характер, яка спрямована на те, щоб матеріально підтримати членів сім’ї (батьків, дітей, дружину) та утриманців загиблого військовослужбовця після втрати близької людини. Особисте розпорядження військовослужбовця на випадок своєї загибелі (смерті) про виплату одноразової грошової допомоги певній особі не є видом заповіту. За своєю сутністю це особисте розпорядження наближене до розпорядження вкладника банку (фінансовій установі) на випадок своєї смерті, що визначене у ч. 1 ст. 1228 Цивільного кодексу України.

Статья посвящена выяснению правовой природы единовременного денежного пособия в случае гибели военнослужащего, а также соответствующего личного распоряжения по поводу этой помощи на случай своей смерти.
Legal nature of single cash aidin the case of the death of a military servant
Keywords: Україна; цивільне право; спадкування; спадщина; спадкодавець; воєнний стан; фізична особа; компенсація збитків; відшкодування шкоди; майно; inheriting; inheritance; testator; martial law; natural person; compensation for losses; compensation for damage; property; одноразова грошова допомога у разі загибелі військовослужбовця; військовослужбовці; загибель військовослужбовця; military personnel; death of a military servant